An article of transdermic medication delivery contraptions for Diabetes management - Meenakshi; Charu Saxena (Revista Electronica de Veterinaria, 2024)
Diabetes mellitus is a chronic condition characterized by insufficient pancreatic insulin production or the body's ineffective utilization of insulin. Currently, over 415 million individuals are affected globally, with projections indicating that this number may rise to 642 million by 2040. The World Health Organization projects that diabetes will be the seventh leading cause of death by 2030. Current diabetes management strategies encompass oral hypoglycemic agents and insulin administration, both of which frequently necessitate substantial patient adherence. Transdermal systems for diabetes treatment have garnered attention in recent years as a viable alternative, offering advantages over oral medications and injections. This review presents recent advancements in transdermal research focused on enhancing diabetes management. Numerous technologies and techniques have been investigated and applied in transdermal systems for the treatment of diabetes. Research indicates that transdermal devices enhance bioavailability relative to oral delivery by circumventing first-pass hepatic metabolism and facilitating a continuous drug release pattern. Transdermal devices improve patient compliance by decreasing dose frequency and effectively regulating blood glucose levels over a prolonged duration. The transdermal system offers notable advantages compared to the oral route for the administration of antidiabetic medications and the biosensing of blood glucose levels, indicating potential improvements in clinical outcomes for diabetes management.